OUTCOME OF OPEN VERSUS CLOSED SURGICAL TECHNIQUE FOR TREATMENT OF CHRONIC PILONIDAL SINUS: A RANDOMIZED CONTROL TRIAL - Sayed Tahir Ali Shah; Mohammad Tahir; Mohammad Nasir; Sohail Aziz Paracha; Khizar Wahab (Khyber Medical University Journal, 2013)
OBJECTIVE: To compare the outcome of “excision with leaving open” versus “excision with primary closure” of chronic pilonidal sinus (PNS) of saccrococygeal area in terms of hospital stay, wound healing, return to work and postoperative complications.